Malnutrition in Tanzania - Malnutrition in Tanzania (Tanzania Italian-Tanzanian Health cooperation programme, 1985)
"Malnutrition is associated with an inadequate diet, poor health and sanitation services, and insufficient care for young children. A combination of income growth and nutrition interventions are therefore suggested to adequately tackle this issue, yet evidence to support this claim is often not available, especially for African settings. The authors evaluate the joint contribution of income growth and nutrition interventions toward the reduction of malnutrition. Using a four-round panel data set from northwestern Tanzania they estimate the determinants of a child's nutritional status, including household income and the presence of nutrition interventions in the community. The results show that better nutrition is associated with higher income, and that nutrition interventions have a substantial beneficial effect. Policy simulations make clear that if one intends to halve malnutrition rates by 2015 (the Millennium Development Goals objective), income growth will have to be complemented by large-scale program interventions. "--World Bank web site.
Keywords: Mlnutrition; Nutrition; Income